Structural Characteristics and Deformation Evolution of an Intra-Continental Fold-Thrust Belt in Eastern Sichuan: Insights Into Analogue Sandbox Models - Wang, Yang-Shuang; Xu, Mo; Yang, Yan-Na; Xia, Qiang; Jiang, Bing; Yang, Chang; Zhang, Heng (Frontiers in Earth Science, 2022)
The Eastern Sichuan area is a typical fold-and-impulse zone. It is bounded by the Qiyue Mountain fault, with septal folds on the east and on the west. Based on previous geological mapping and surface geological structure research as well as the fault-related folding theory, in this study, tectonophysical simulation experiments were conducted to investigate the tectonic geometry and kinematics of the Eastern Sichuan fold-impulse zone. The experiments were conducted by selecting different experimental materials and changing the physical properties of the cover, the friction between the cover and the basement, the number of slip layers, the burial depth, and other factors. Finally, the similarity of the results to the morphological characteristics of the real geological structure was assessed. The results show that the deformation style is influenced to some extent by the brittle shear strength and the ductile shear strength of the basement, and the different interlayer cohesions between the competent and incompetent layers, the high rheology, and the burial depth of the slickensides played crucial roles in the formation of the final evolution of the Eastern Sichuan fold fault zone. The step-like system, composed of a lower crustal crystalline basement detachment surface, regional boundary fractures, and the overlying Cambrian and Triassic synclines, is a necessary condition for the formation of the Eastern Sichuan fold and fault zone and controls the overall evolution of the zone. Under the action of multiple phases of tectonic activity with different main stress orientations, the geological phenomenon of multiple superimposed phases of folding in different directions observed at present in the Eastern Sichuan area was formed. The well-developed karst features are not conducive to the construction of a project tunnel in the area where tightly closed back-slope, fissures, and normal faults have developed in the Eastern Sichuan fold and fault zone.